PENGARUH TIMBAL BALIK ANTARA PEMBAYARAN DIVIDEN DAN PERTUMBUHAN MODAL SENDIRI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sofiati Subagio; Yenni Kurnia Gusti (Universitas Ahmad Dahlan, 2016)
This study extends previous research on dividend policy and funding decisions using structural equation modeling. Previous studies have focused on dividend policy or funding decisions alone, to determine the factors that influence by using multiple linear regression. This study aims to determine the mutual influence between dividends and capital growth. The authors would like to prove that there are similarities between the factors that affect the payment of dividends and capital growth include profitability, agency cost of debt, and retained earnings. In this research, the sample used is 72 shares activitely traded and has been listing between periods 2009-2013 in Indonesia Stock Exchange. The test results demonstrate the usefulness of the model testing using indicators overall goodness of fi t to meet the criteria recomended level of fitness. By using the non-statistical measure such absolute goodness of fit and parsimony goodness of fi t value exceeds recomended levels, it has indicated a good fit between the data with the model proposed research.